Some iterative methods for quasi-equilibrium problem s - Strodiot, Jean-Jacques (Trường Đại học Đà Lạt, 2014)
In this paper we present two new extensions of Korpelevich's extragraclient method for solving the scalar Quasi-Equilibrium Problem (QEP) in Euclidean space. In both extensions we replace the second orthogon al p rojection in the correction step of the extragradient method by an Armijo linesearch adapted to (QEP). We show that in both extensions we obtain, under mild conditions and without a Lipschitz condition, the global convergence of our iterative met h o d s for computing a quasi-equilibrium solution.